(untitled) (Research, Society and Development, 2022)
The food industry has been looking for alternatives to add fiber and other nutritional properties to products. The aim of this article was to investigate the potential of products formulated from young-aged bamboo culms and shoots for human consumption. This is an integrative review article, built from the study of scientific articles available in the databases of the CAPES Journal Portal, using the following descriptors ’bamboo shoot’, ’young bamboo culm’, ’food industry’, ’flour’, ’biscuits’, ’cookies’, and ’nuggets’, both used in combinations, in the period between 2015 and 2022. Eight scientific papers were selected, a study for each year of the period of interest, which describe the use of young bamboo culms and shoots in fiber, flour and starch-based food products. It is noticed that in recent years the use of young bamboo culms and shoots has aroused the interest of the scientific community, mainly due to its high nutritional value, antioxidant capacity, good sensory acceptance, reduced fat and sugar content, stimulating the emergence of the market consumer. For the present moment, the use of young bamboo culms and shoots in culinary preparations is sufficiently tested and adds nutritional value to bakery and pastry formulations and to animal products such as dairy and meat products.